Divergent evolution and evolution by the birth-and-death process in the immunoglobulin VH gene family - OTA, T; NEI, M (Molecular biology and evolution, 1994)
Immunoglobulin diversity is generated primarily by the heavy- and light-chain variable-region gene families. To understand the pattern of long-term evolution of the heavy-chain variable-region (VH) gene family, which is composed of a large number of member genes, the evolutionary relationships of representative VH genes from diverse organisms of vertebrates were studied by constructing a phylogenetic tree. This tree indicates that the vertebrate VH genes can be classified into group A, B, C, D, and E genes. All VH genes from cartilaginous fishes such as sharks and skates from a monophyletic group and belong to group E, whereas group D consists of bony-fish VH genes. By contrast, group C includes not only some fish genes but also amphibian, reptile, bird, and mammalian genes. Group A and B genes were composed of the genes from mammals and amphibians. The phylogenetic analysis also suggests that mammalian VH genes are classified into three clusters--i.e., mammalian clans I, II, and III-and that these clans have coexisted in the genome for >400 Myr. To study the short-term evolution of VH genes, the phylogenetic analysis of human group A (clan I) and C (clan III) genes was also conducted. The results obtained show that VH pseudogenes have evolved much faster than functional genes and that they have branched off from various functional VH genes. There is little indication that the VH gene family has been subject to concerted evolution that homogenizes member genes. These observations indicate that the VH genes are subject to divergent evolution due to diversifying selection and evolution by the birth-and-death process caused by gene duplication and dysfunctioning mutation. Thus, the evolutionary pattern of this monofunctional multigene family is quite different from that of such gene families as the ribosomal RNA and histone gene families.